Etika Kepustakawanan: Suatu pendekatan terhadap kode etik pustakawan Indonesia - Rachman Hermawan, Zulfikar Zen (Sagung Seto, 2010)
Etika Kepustakawanan: Suatu pendekatan terhadap kode etik pustakawan Indonesia